Aflatoxin exposure among children of age 12-59 months in Butajira District, South-Central Ethiopia: A community based cross-sectional study - Ayele, M.; Haile, D.; Alonso, Silvia; Sime, H.; Abera, A.; Balcha, K.H.; Roba, K.T.; Guma, G.T.; Endris, B.S. (Springer, 2022)
Background The continued provision of safe food, free of aflatoxin remains a huge challenge in developing countries. Despite several favourable climatic conditions that facilitate aflatoxin contamination in Ethiopia, there is little information showing aflatoxin exposure in children. Therefore, this study assessed aflatoxin exposure among young children in Butajira district, South-Central Ethiopia. Methods Community based cross-sectional study stratified by agro-ecology was employed in Health and Demographic Surveillance Site (HDSS) of Butajira. The study included 332 children aged 12–59 months and were selected by simple random sampling technique using the HDSS registration number as a sampling frame. We collected data on dietary practice and aflatoxin exposure. Aflatoxin M1 concentration in urine was measured by Enzyme-Linked Immunosorbent assay (ELISA). The data analysis was carried out using STATA. Results Detectable urinary Aflatoxin M1 was found in 62.4% (95% CI: 56.9 – 67.5%) of the children at a level ranging from 0.15 to 0.4 ng/ml. Children living in lowland agro-ecological zone had [AOR = 2.11 (95% CI; 1.15, 3.88] odds of being exposed to aflatoxin as compared to children living in highland agro-ecological zone. Children at lower socio-economic status [AOR = 0.27 (95% CI; 0.14, 0.50] and medium socio-economic status [AOR = 0.47 (95% CI; 0.25, 0.87] had 73% and 53% lower odds of being exposed to aflatoxin as compared to children in the higher socio-economic status, respectively.